Results with Floxuridine, Actinomycin D, Etoposide, and Vincristine in Gestational Trophoblastic Neoplasias with International Federation of Gynecology and Obstetrics Scores ≥5. (9th September 2021) - Li, Yuan; Kong, Yujia; Wan, Xirun; Feng, Fengzhi; Ren, Tong; Zhao, Jun; Yang, Junjun; Xiang, Yang
Abstract : Background: 5-fluorouracil-based multiagent chemotherapy has been used as the primary treatment for high-risk gestational trophoblastic neoplasia (GTN) in China for a few decades. This study aims to assess the efficacy and toxicity of floxuridine, actinomycin D, etoposide, and vincristine (FAEV) as a primary treatment for patients with GTN who had International Federation of Gynecology and Obstetrics (FIGO) scores ≥5. Materials and Methods: A total of 207 patients with GTN who had FIGO scores ≥5 were treated with FAEV as first-line chemotherapy at Peking Union Medical College Hospital between January 2002 and December 2017. Complete remission (CR), resistance, survival, toxicity, and reproductive outcomes were analyzed. Results: Of the 207 patients treated with FAEV, 9 (4.3%) required a change of chemotherapy owing to toxicity and 1 (0.5%) died of cerebral hernia 5 weeks after commencing treatment. The remaining 197 patients were assessable to determine the response to FAEV; among them, 168 (85.3%) achieved CR with FAEV and 29 (14.7%) developed resistance to FAEV. The 5-year overall survival rate of the entire cohort was 97.4%. Grade 3–4 neutropenia, thrombocytopenia, and anemia occurred in 28.4%, 6.8%, and 6.2% of cycles, respectively. No acute toxicity-related deaths occurred. Five patients developed acute myeloid leukemia 10–50 months after exposure to chemotherapy; another patient developed duodenal cancer 2 years after completing therapy. Sixty-one patients who preserved fertility wanted to become pregnant; 56 of them conceived. Conclusion: The FAEV regimen is an effective primary treatment for patients with GTN who have FIGO scores ≥5 and has predictable and manageable toxicity. Implications for Practice: The most commonly used multiagent chemotherapy for high-risk gestational trophoblastic neoplasia (GTN) is etoposide, methotrexate and actinomycin D/cyclophosphamide and vincristine (EMA/CO) worldwide. However, 5-fluorouracil-based multiagent chemotherapy has been used as a primary treatment for high-risk GTN in China for a few decades. This study evaluated the efficacy and toxicity of floxuridine, actinomycin D, etoposide, and vincristine (FAEV) as a primary treatment for patients with GTN who have International Federation of Gynecology and Obstetrics (FIGO) scores ≥5. The study's data demonstrated that FAEV as a primary treatment achieved favorable outcomes for patients with FIGO scores ≥5. Toxicities that result from the FAEV regimen are predictable and manageable. The FAEV regimen may provide another option for the treatment of GTN.